2014
DOI: 10.4236/ajps.2014.515233
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Forage Clipping Stages and Different Levels of Nitrogen on Grain and Forage Yields of TRITICALE (× TRITICOSECALE WITTMACK)

Abstract: In order to reach suitable forage clipping and estimate nitrogen fertilizer to most economical proficiency, an experiment was carried out at Saatlo Station in 2008-2009 seasons. A factorial experiment was done based on the randomized complete blocks design with 4 replications. The first factor was three levels of clipping stages including non-clipping, clipping at tillering and booting stages. Different levels of nitrogen fertilizer including 0, 40, 80, 120 and 160 kg/ha were arranged at the second factor. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…m -2 with significant (C x N) effect. Niazkhani et al, (24) observed not significant (C x N) effect in triticale. In the (V x C) interaction maximum spike.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…m -2 with significant (C x N) effect. Niazkhani et al, (24) observed not significant (C x N) effect in triticale. In the (V x C) interaction maximum spike.…”
Section: Resultsmentioning
confidence: 91%
“…Afridi et al, (1) observed that wheat harvest index significantly increased with fertilizer-N treatments, while the cutting stress significantly decreased harvest index with no significant interaction among the variables was observed in this trait. Niazkhani et al, (24) observed significant effects in C, N and (C x N) in triticale. In the (V x C) interaction maximum harvest index of 0.365 and 0.492 were obtained from interaction of Ibba-99 with no cut and cut 2 , while lowest values (0.086, 0.082) were obtained from Local variety and cut (C 3 ) for Bakrajo and Bazyan locations, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations